Building Noble Character Through The Habit of Reciting Asmaul-Husna At Madrasah Ibtidaiyah Negeri 1 Pasaman Barat - Rifana, Fitria; Yanti, Silvia Rahma; Amelia, Ulfi (Fahmina: Jurnal Pendidikan Islam, 2024)
The cultivation of noble character during the elementary school years is an appropriate time for character development. At this stage, children begin to explore their external environment, which exposes them to various influences, including negative ones. Without proper guidance and direction, these influences may lead to moral degradation. Several cases were reported at MIN 1 Pasaman Barat regarding moral issues among students before the implementation of character development activities. These issues included lack of discipline in adhering to school rules, low motivation and academic performance, inappropriate speech, disobedience toward teachers, and rough behavior toward peers. These challenges highlight the need for character-building efforts among students at MIN 1 Pasaman Barat. This study aims to investigate the urgency, outcomes, and application of Asmaul Husna recitation practices in fostering noble character development at MIN 1 Pasaman Barat. A qualitative descriptive approach was employed in this research. Data collection methods included observation, interviews, and documentation. The data were analyzed using critical analysis techniques. The research findings indicate that the practice of reciting Asmaul Husna contributes significantly to the cultivation of noble character values in students’ daily behavior. At MIN 1 Pasaman Barat, this activity is considered an act of worship for every Muslim, bringing blessings, opening students' hearts during the learning process to facilitate the acceptance of truth, and improving their fluency in reciting Asmaul Husna. Additionally, it encourages the practice of the 99 names of Allah (Asmaul Husna) in daily life.